Percutaneous Aspiration Thrombectomy: A Promising Approach to Catch a Cardiopulmonary Thrombus-in-Transit - Phuong-Uyen Vo; Charles Matriano-Lim; Grace Ayafor (Annals of Internal Medicine: Clinical Cases)
Clot-in-transit (CIT) is a life-threatening emergency that occurs in about 25 000 patients annually in the United States and is associated with high mortality due to the potential for rapid cardiopulmonary collapse, requiring prompt interventions. We present a case of a right atrial clot-in-transit extending from an existing inferior vena cava (IVC) filter in a patient with pulmonary embolism who had a successful aspiration thrombectomy using a percutaneous catheter-based system, highlighting the benefit of this technology in treating cardiopulmonary thrombi, especially in high-risk patients.